Resting-state functional connectivity and socioemotional processes in male perpetrators of intimate partner violence against women - Sofia Amaoui; Cristina Martín-Pérez; Agar Marín-Morales; Natalia Bueso-Izquierdo; María Ángeles García-León; Miguel Pérez-García; Juan Verdejo-Román (Scientific Reports, 2022)
Abstract Intimate partner violence against women (IPVAW) is a serious and overwhelming public concern. Neuroimaging techniques have provided insights into the brain mechanisms underlying IPVAW perpetration. The purpose of this study is to examine the resting-state functional connectivity (rsFC) involving the process of social decision-making of male perpetrators. Twenty-six male perpetrators convicted for an IPVAW crime were compared to 29 men convicted for crimes other than IPVAW (other offenders) and 29 men with no criminal records (non-offenders) using a seed-based approach. Seeds were located in areas involved in reflective (prefrontal), impulsive (amygdala and striatum) and interoceptive (insula) processing. Then, as an exploratory analysis, the connectivity networks on male perpetrators were correlated with measures of executive functions and socioemotional self-report measures. Male perpetrators in comparison to other offenders and non-offenders, presented higher rsFC between prefrontal, limbic, brainstem, temporal and basal ganglia areas. Also male perpetrators showed higher rsFC between insula, default mode network and basal ganglia, while lower rsFC was found between prefrontal and motor areas and between amygdala, occipital and parietal areas. Exploratory correlations suggest that the specific rsFC in male perpetrators might be more related to socioemotional processes than to executive functions. These results showed that male perpetrators present a specific rsFC in brain systems that are essential for an adaptive social decision-making.